The Influence of The Level of Seller's Trust on consumers toward the Cod Payment Transaction system indonesia (case Study of Students of Polytechnic State of Bengkalis) - Faiza, Yuli Nor (Inovbiz: Jurnal Inovasi Bisnis Seri Manajemen, Investasi dan Kewirausahaan, 2024)
In recent years, the use of the internet has become increasingly popular. With the rapid development of technology today, one of which is the development of the internet, it has a huge impact on all aspects of life such as the business sector. Online shopping is one of the most popular payment methods for online buying and selling transactions. Cash on Delivery (COD) is a payment method that is widely used by business people as a strategy in attracting buyers or finding customers so as to increase sales of their productsKeywords: Â Trust Sellers, Consumers, COD System.